Analisis Pola Persebaran Minimarket dan Aspek Geografi yang Mempengaruhinya di Kecamatan Padang Utara - Pratama, Yoga Edi (JURNAL BUANA, 2025)
This study aims to analyze the shape of the distribution pattern of minimarkets in North Padang District. The research approach used is a quantitative approach. The sampling method used is total sampling consisting of 44 locations of minimarket units. Nearest Neighbor Analysis technique is used to achieve the analysis objectives. The results of the analysis of the distribution pattern of the existing minimarket locations show that the shape of the distribution pattern is a clustered pattern.